2015
DOI: 10.24297/jac.v11i5.4471
|View full text |Cite
|
Sign up to set email alerts
|

Markers characterizing corneal damage during aging of rat

Abstract: Aging is a biological phenomenon that involves an increase of oxidative stress associated with gradual degradation of the structure and function of the cornea. Gender differences and subsequent deterioration of cornea is an interesting topic, especially yet few data are available concerning the impact of age, especially on the corneal. One hundred male and female Wistar albino rats ages 3, 6, 18, 24, and 30 months (n=10 equal for male and female) were used. At the time interval, cornea were investigated by lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…In case of diabetic and hypercholesterolemic group, there was a detected increase of neovascularization explained by numerous spaced regions outlined internally by flattened cells suspected endothelial cells as well as degeneration of the endothelium lining the Descemet's membrane (DM). Hypercholesterolemic showed the least damage comparing with diabetes and or hypercholesterolemia (Figures 2-5) Similar findings were reported in cornea of 24 & 30 M old rats [56]. Diabetic patients, KKAy mice, rat and monkey exhibited pronounced alterations in corneal epithelium, fragility of collagenous stroma and degeneration of keratocytes [57][58][59][60].…”
Section: Discussionsupporting
confidence: 73%
“…In case of diabetic and hypercholesterolemic group, there was a detected increase of neovascularization explained by numerous spaced regions outlined internally by flattened cells suspected endothelial cells as well as degeneration of the endothelium lining the Descemet's membrane (DM). Hypercholesterolemic showed the least damage comparing with diabetes and or hypercholesterolemia (Figures 2-5) Similar findings were reported in cornea of 24 & 30 M old rats [56]. Diabetic patients, KKAy mice, rat and monkey exhibited pronounced alterations in corneal epithelium, fragility of collagenous stroma and degeneration of keratocytes [57][58][59][60].…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, other authors also reported an alteration in the primary synaptic receptors associated to a pupillary opening decrease, retina thinning and ganglion cells degeneration , associated to a VEP′s elongation in NHP. In this context, it has also been described that aging is associated with structural and functional corneal changes such as transparency, which alter their capacity to refract light, and also to protect the eye internal structures . Morphological studies have demonstrated an age‐related decrease in endothelial cell density and indicate that the endothelium in vivo either does not proliferate at all or proliferates at a rate that does not keep pace with the rate of cell loss.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their limited number, previous experimental studies assessed the effects of onion extracts on corneal changes related to different animal models [18,28], in addition to the effects of onion extracts on the pathological changes of other ocular structures [19,29,30]. Furthermore, several publications indicated that age has major changes on the cornea [31][32][33][34][35]. In accordance with our results, El-Sayyad et al [33] and Halawa [34] found that the cornea of aged rats exhibited atrophied epithelium with small dark nuclei, hyalinization of the stromal collagen fibrils, keratocystic loss and degeneration of the lining endothelium.…”
Section: Discussionmentioning
confidence: 99%